Membrane filtration reduces nutrient availability and invasion potential in drinking water systems, without affecting mature biofilms - Pluym, Thomas; Waegenaar, Fien; Dejaeger, Karlien; Dhoore, Marie; Mestdagh, Eline; Cornelissen, Emile; Boon, Nico; De Gusseme, Bart (Frontiers in Microbiology, 2025)
Ensuring biostable drinking water is a growing priority for drinking water utilities, especially in non- or minimally chlorinated distribution systems where microbial regrowth is controlled through nutrient limitation. In this study, we evaluated the efficacy of ultrafiltration (UF) and nanofiltration (NF) in reducing total organic carbon (TOC) and their impact on the microbiology in a pilot-scale drinking water distribution system over 7 weeks. NF achieved significantly higher TOC removal (75.4%) compared to UF (25.4%), with high performance size exclusion chromatography revealing almost complete removal of all molecular weight fractions in NF-treated water. When introduced into the pilot system, NF-, UF-treated water, and untreated tap water supported similar increasing bulk cell concentrations, but exhibited distinct bacterial community compositions, with NF-treated water showing the most divergent microbiome. Despite these differences in the bulk water, the mature biofilm community (~2 years old) remained stable, underscoring it resilience to changes in nutrient conditions. An invasion assay demonstrated that decay rates of unwanted microorganisms increased with decreasing organic carbon content. For example, decay rates for the introduced microorganism Pseudomonas putida in NF-, UF- treated water, and untreated tap water were respectively, −0.18 h−1, −0.143 h−1, and −0.089 h−1, indicating enhanced biostability in membrane-treated systems.